New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Section: xviii, 278 p
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

De l'indécence aux hommes d'accoucher les femmes, et ; De l'obligation aux mères de nourrir leurs enfants, suivi de ; S'il est des signes qui assurent de la puissance des hommes, autant que le font ceux qui répondent de la sagesse des filles 1707 - Hecquet, Philippe (Côté-femmes, 1990)
Première publication 1744
Keywords: 1700-1799; cours; discipline; europe; fem1000; france; histoire; premier cycle; périodes historiques; régions géographiques; santé; santé reproductive; sciences humaines; thématiques